KARAKTERISTIK NARATIF DAN RETORIKA PENGUNGKAPAN MODAL INTELEKTUAL DALAM LAPORAN TAHUNAN PERUSAHAAN PERBANKAN BUMN DI INDONESIA - Umar Hamdan Nasution (Journal Economic Management and Business, 2026)
Intellectual capital disclosure (ICD) has evolved into a strategic instrument for corporate transparency since the enactment of PSAK No. 19. While previous studies focused heavily on quantitative indexing, the methodological novelty of this study lies in transitioning toward qualitative content analysis to decode narrative traits and implicit impression management. This study aims to evaluate the qualitative nature and rhetorical strategies embedded within the integrated annual reports of the four largest state-owned (BUMN) banking companies in Indonesia. Using a tiered coding mechanism, results indicate that despite massive digital investments driving granular monetary reporting in structural capital, human and relational capitals remain predominantly descriptive-normative. Furthermore, banks strategically shift narrative tones toward a forward-looking orientation as an impression management tool to obscure short-term financial performance fluctuations. This study provides crucial empirical insights for regulators to standardize narrative reporting frameworks for intangible assets.